Contribution of Giant Aneurysm of a Membranous Ventricular Septal Defect to Right Ventricular Outflow Tract Obstruction - Altunbas, Gokhan; Gokaslan, Gokhan; Ercan, Suleyman; Davutoglu, Vedat; Deniz, Hayati (The Thoracic and Cardiovascular Surgeon, 2013)
Perimembranous defects are the most common types of ventricular septal defects (VSDs). In many cases, an aneurysm accompanies this defect. The aneurysm can have advantageous consequences on defect hemodynamics. However, it also has numerous complications that are frequently encountered in clinical practice. In this case, we describe a patient with a membranous VSD with giant aneurysm formation contributing to subpulmonic severe obstruction.
Keywords: ventricular septal defect aneurysm; echocardiography; right ventricular outflow tract obstruction